Robotic pediatric surgery: Early experience in Brazil - G.F. Paganoti; F. Barros; M.A.G. Bueno; G.C. Guimaraes; A.M. Vieira; C.L. Costa; M.L.P. Apezzato (Elsevier, 2021)
Introduction: Although well-established in a variety of adult surgical subspecialties, robotic surgery is still gaining ground in Pediatric Surgery. Some of the technical limitations of laparoscopy have been overcome by the high-quality 3D vision and freedom movement of the robotic arms. The present study describes the initial experience with the first thirteen pediatric robotic surgeries performed by a single surgeon, under the supervision of the same proctor. Material/methods: Case series retrospectively presenting the initial experience with pediatric robotic surgery in Brazil from 2017 to 2020. Results: Thirteen cases were reviewed, 8 female and 5 male, the average age was 6 years (2-12), and weight ranged from 11,400 to 78,200 g (median 18600g). Oncological diseases were the main diagnosis (11 patients) and 2 had benign conditions (1 gastroesophageal reflux and 1 choledochal cyst). No conversion to open surgery was necessary. The average length of stay in the ICU was 3 days (1-5 days), and time to hospital discharge was 4.8 days (1-10 days). In 30.7% of the cases there has been respiratory complications. No major complication requiring a surgical approach in the postoperative period and no deaths related to robotic surgery were identified. In 90% of the oncological patients, complete resection without recurrences has been possible. Conclusion: Robotic surgery is feasible and safe in pediatrics. A great variety of surgeries are amenable to be accomplished robot-assisted with minor surgical complications.